UI/UX DESIGN FOR A WEB-BASED DONOR ATTENDANCE SCHEDULING APPLICATION AT GRIYA YATIM AND DHUAFA AL-FALAH RANCAEKEK ORPHANAGE - Asep Akbar; Hendra Gunawan (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Griya Yatim and Dhuafa Al-Falah Rancaekek Orphanage is a social institution engaged in the care, education, and mentoring of orphans and underprivileged children. In sup- porting the sustainability of these activities, the role of donors is very important, both in the form of financial contributions and direct participation in orphanage activities. However, the process of scheduling donor visits is still carried out manually, which of- ten leads to problems such as irregular schedules, time conflicts, and suboptimal re- cording of attendance data. Therefore, a solution is needed in the form of designing a User Interface and User Experience (UI/UX) for a web-based donor visit scheduling application that is easy to use and aligned with user needs. The purpose of this study is to design the UI/UX of a donor visit scheduling application to improve usability and ef- ficiency in data management. The method used is Human Centered Design (HCD), which focuses on user needs and experiences, with stages consisting of inspiration, ide- ation, and implementation. Data collection methods include observation, interviews, and literature studies to understand user needs and the existing system workflow. The result of this study is a UI/UX design of a web-based donor visit scheduling application that includes interface design and user interaction flows, such as donor data manage- ment, visit scheduling, schedule notifications, and attendance reports. This design is ex- pected to provide a better user experience and assist orphanage administrators in man- aging donor attendance more effectively, systematically, and efficiently.